Investigation of association between LINC00673 rs11655237 C>T and Wilms tumor susceptibility. Issue 7 (1st July 2019) - Gao, Xiaofeng; Jia, Wei; Zhu, Jinhong; Fu, Wen; Zhu, Shibo; Xia, Huimin; He, Jing; Liu, Guochang
Abstract : Background: Wilms tumor (WT) is the most common pediatric renal malignancy. Previous genome‐wide association studies have identified that the LINC00673 rs11655237 C>T polymorphism is associated with the risk of several types of cancer. However, few studies have investigated the association between LINC00673 rs11655237 C>T and WT susceptibility. Method: We genotyped LINC00673 rs11655237 C>T in 145 patients with WT and 531 cancer‐free controls recruited from southern Chinese children. The strength of association was estimated by odds ratios (ORs) and 95% confidence intervals (CIs). Results: Our study indicated that there was no significant association between LINC00673 rs11655237 C>T polymorphism and WT risk under all the tested genetic models (CT vs CC: adjusted OR = 0.94, 95% CI = 0.63‐1.40; TT vs CC: adjusted OR = 0.60, 95% CI = 0.22‐1.59; TT/CT vs CC: adjusted OR = 0.89, 95% CI = 0.61‐1.31; and TT vs CC/CT: adjusted OR = 0.61, 95% CI = 0.23‐1.61). Further stratified analysis detected no significant association, either. Conclusion: In conclusion, we failed to find any association between the LINC00673 rs11655237 C>T polymorphism and WT risk. This finding needs to be verified in larger studies and other populations.